2022
DOI: 10.1212/nxi.0000000000001180
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Hyperreflecting Foci Associate With Cortical Pathology in Multiple Sclerosis

Abstract: Background and ObjectivesMicroglia, the resident immune cell of the brain and retina, is widespread activated in the white and gray matter (GM) in multiple sclerosis (MS). The objective of this study is to evaluate the presence and number of hyperreflecting foci (HRF), considered clusters of activated and proliferating retinal microglia, and their association with clinical and radiologic disease parameters in relapsing-remitting MS (RRMS).MethodsAt baseline, 80 patients with RRMS underwent optical coherence to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 50 publications
2
14
1
Order By: Relevance
“…Inasmuch as a widespread microglial activation has been demonstrated by histological and neuroimaging (advanced MRI and PET techniques) studies in MS ( 26 ), this disease may constitute an ideal pathological field, where the origin of HRF is clarified and microglial behavior during the course of CNS inflammatory disorders is analyzed. In a previous study, we found that INL HRF count correlated with both inflammatory cortical pathology and INL thickness, suggesting HRF parallel gray matter rather than white matter damage in RRMS ( 6 ). These findings were in line with histological observations supporting a pivotal role for microglia and a marginal role for T cells in both retinal and cortical pathology in MS ( 27 ).…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…Inasmuch as a widespread microglial activation has been demonstrated by histological and neuroimaging (advanced MRI and PET techniques) studies in MS ( 26 ), this disease may constitute an ideal pathological field, where the origin of HRF is clarified and microglial behavior during the course of CNS inflammatory disorders is analyzed. In a previous study, we found that INL HRF count correlated with both inflammatory cortical pathology and INL thickness, suggesting HRF parallel gray matter rather than white matter damage in RRMS ( 6 ). These findings were in line with histological observations supporting a pivotal role for microglia and a marginal role for T cells in both retinal and cortical pathology in MS ( 27 ).…”
Section: Discussionmentioning
confidence: 81%
“…All MS patients underwent spectral domain OCT (Spectralis; Heidelberg Engineering, Carlsbad, CA; Heidelberg Eye Explorer version 1.7.0.0) examination of both eyes, in a dark room without the injection of any mydriatic agent. In line with recent publications ( 3 , 6 , 14 ), the analysis of the central linear scan of the macular map, crossing the fovea, was considered for HRF counting. HRF were counted in the area included between two perpendicular lines to Brunch’s membrane traced at 1,500 μm both temporally and nasally from the center of the fovea.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, the neurodegenerative component of the disease has been re‐emphasized; manifold neuropathological and advanced neuroimaging studies have shown cortical lesions and cortical and deep gray matter damage from the earliest disease stages that contribute significantly to long‐term disability, including cognitive impairment 37–39 (Figure 1). Also, the optic nerve and retina, which are part of the CNS, are frequently affected from early on, as mirrored by numerous optical coherence tomography (OCT) studies showing retinal atrophy with loss of axons and retinal ganglion cells in eyes with and without prior optic neuritis 40–43 . Lesions and more subtle tissue damage in the spinal cord that predominantly manifest in the cervical cord significantly contribute to disability, especially impaired ambulation with reduced walking distance and bowel–bladder problems 44 (Figure 1).…”
Section: Immune Neurological and Metabolic Dysfunctions In Msmentioning
confidence: 99%